Pengaruh viral marketing dan endorser terhadap keputusan pembelian dengan brand awareness sebagai variabel intervening - Anggi Irawan; Irwan Misbach (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2020)
This study aims to examine the direct and indirect effects of viral marketing on endorsers on purchasing decisions mediated by brand awareness as mediation. This research is a type of quantitative research with an associative approach. The population in this study were users of Oppo smartphone products in Makassar City. The sampling technique used accidental sampling and purposive sampling. The number of samples was 100 respondents using the Hair formula. The data used are primary data derived from questionnaire answers. Data analysis used Path Analysis with the help of SPSS 21. The results showed that viral marketing and endorsers had a positive and significant effect on brand awareness. Furthermore, viral marketing, endorsers and brand awareness directly have a positive and significant effect on purchasing decisions. In addition, the results of this study also show that brand awareness is able to mediate the relationship between viral marketing and endorsers on purchasing decisions. The implication of this research needs to be reinforced in product promotion so that consumers are able to remember products continuously which can have an impact on product purchasing decisions.